Airway Cam video series - Levitan, Richard M.; Airway Cam Technologies (Wayne, PA : Airway Cam Technologies, 1998)
Demonstrates real intubations and reviews the anatomic differences between infants, children and adults, as well as pediatric equipment selection and practical techniques with different blades
V. 2 ( Pediatric intubation )
Videocassette is available at Koleksi Media Perpustakaan HUKM
Keywords: Intubation, Intratracheal -- methods; Intubation, Intratracheal -- instrumentation; Anesthesia -- methods